Land-use changes and the expansion of biofuel crops threaten the giant anteater in southeastern Brazil - Bertassoni, Alessandra [UNESP]; Costa, Rômulo Theodoro [UNESP]; Gouvea, Jéssica Abonizio [UNESP]; Bianchi, Rita De Cassia [UNESP]; Ribeiro, John Wesley [UNESP]; Vancine, Maurício Humberto [UNESP]; Ribeiro, Milton Cezar [UNESP] (Oxford University Press (OUP), 2019)
Land-use changes impact biodiversity, and biofuel crop production and its expansion pose as an important driver of negative effects in the tropics. Understanding the influence of land-use changes on suitable habitats for species is a worldwide conservation challenge, particularly on large-sized mammals. We modeled habitat suitability of the threatened giant anteater (Myrmecophaga tridactyla) in the Brazilian State of So Paulo. The region is the most populous and economically developed of the country and is the world's main sugarcane production area. We aimed to 1) map habitat suitability for the giant anteater population in the State; 2) assess the contributions of selected landscape and anthropogenic predictors to species habitat suitability; and 3) quantify suitable habitats in environmental protection areas and in areas threatened by the sugarcane expansion. We used a two-step analysis: First, we created a suitability map in the species' distributional range (Drange); from this map, we extracted the results for So Paulo State. Second, we built a regional model to predict the current scenario of So Paulo using the following environmental layers: 1) the resulting distributional range map for giant anteater (Drange); 2) landscape metrics; and 3) anthropogenic factors that might affect anteaters. The State of São Paulo presented, in general, very low values of habitat suitability. The following predictors made the greatest contribution: Drange, vegetation connectivity and distance to protected areas. Suitable habitats for anteaters within strictly protected areas are very scarce (1.6% of the total area), and 22% of the suitable areas are expected to be altered by future sugarcane expansion. Suitable habitats on private lands must play a role in conserving biodiversity.
Keywords: Bioethanol; Mammals; Pilosa; Protected areas; Species distribution modeling